STABILITY OF FREQUENCY DISTRIBUTION IN FRAME OF NATURAL PARAMETRIZATION. I - Danielian, E.A.; Arzumanyan, S.K. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
In this paper the stability problem for frequency distribution in frame of natural parameterization is formulated and discussed. The case of finite number of independent parameters is characterized. A corresponding stability problem is investigated in terms of $l_p$-metric.
Keywords: frequency distribution; $l_p$-metric; stability by parameters